(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
The mealybug species Coccidohystrix burumandi Moghaddam, sp. n. is described from the leaves of Euphorbia sp. (Family: Euphorbiaceae) in Iran. The adult female is illustrated in detail. The distribution of the genus Coccidohystrix is briefly discussed in the Palaearctic Region.